A coordination model for interactive components - Barbosa, Marco António (2010)
Although presented with a variety of ‘flavours’, the notion of an interactor, as an abstract characterisation of an interactive com- ponent, is well-known in the area of formal modelling techniques for interactive systems. This paper replaces traditional, hierarchical, ‘tree-like’ composition of interactors in the specification of complex interactive sys- tems, by their exogenous coordination through general-purpose software connectors which assure the flow of data and the meet of synchronisation constraints. The paper’s technical contribution is twofold. First a modal logic is defined to express behavioural properties of both interactors and connectors. The logic is new in the sense that its modalities are indexed by fragments of sets of actions to cater for action co-occurrence. Then, this logic is used in the specification of both interactors and coordination layers which orchestrate their interconnection.